Measuring sustainable forest management in Tierra del Fuego, Argentina - Carabelli, Esteban; Bigsby, Hugh; Cullen, Ross; Peri, Pablo Luis (Taylor & Francis, 2025)
The Tierra del Fuego government has a statutory responsibility to ensure that Nothofagus forests are sustainably used. To provide strategies to maximize the forest's sustainable benefits for society, this research develops indicators of sustainable management of lenga forests. Multicriteria methods are used to integrate different perspectives regarding environmental, social, and economic aspects of the forest's management. Starting with a range of internationally accepted criteria and indicator (C&I) schemes, a local set of C&I was developed to assess the forest's sustainability. The relative importance of the C&I, and the degree to which sustainability was being achieved were assessed using a survey completed at a series of workshops and a follow-up survey. The results show that current management scores an aggregate 2.51 on a range from 1.0 to 5.0, where 1.0 for any indicator means that the indicator is close to a critical threshold value (ability of the ecosystem to recover) and 5.0 is far from this threshold value. The results also show that the key areas to work on are in policy and planning, resource administration, monitoring of resource use, and public information about, and involvement in, forest use.